2010
DOI: 10.1007/dcr.0b013e3181dadeb4
|View full text |Cite
|
Sign up to set email alerts
|

Fewer Than 12 Lymph Nodes Can be Expected in a Surgical Specimen After High-Dose Chemoradiation Therapy for Rectal Cancer

Abstract: With a standardized surgical technique and pathologic evaluation, the number of lymph nodes present after neoadjuvant chemoradiation and total mesorectal excision for rectal cancer varies greatly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 25 publications
4
31
2
2
Order By: Relevance
“…A study from our institution showed that after neoadjuvant therapy, the mean lymph node harvest is 10.1 (range, 1-38), which coincides with our data [16]. The mean specimen length was 33.7 cm (range, 16-117 cm).…”
Section: Pathologysupporting
confidence: 77%
“…A study from our institution showed that after neoadjuvant therapy, the mean lymph node harvest is 10.1 (range, 1-38), which coincides with our data [16]. The mean specimen length was 33.7 cm (range, 16-117 cm).…”
Section: Pathologysupporting
confidence: 77%
“…The normal mesorectal fibro-fatty tissue also atrophies due to radiation induced fibrosis. These factors confound to make it difficult to recognize lymph nodes in irradiated specimen by gross examination (17,32,34,35). In addition, the lymphoid tissue is highly sensitive to radiation and shows more rapid apoptosis, leading to more favourable response than rectal wall thickness (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Although, the standardized treatment including preoperative chemo-radiation followed by TME and complete pathological evaluation is unanimously followed worldwide, but the number of lymph nodes harvested varies greatly with ranging 29% to 72% (17,(29)(30)(31)39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a retrospective analysis of 1098 patients who underwent CRC resection, Thomas and colleagues 17 found that 41% were staged as Dukes C. Sixty-four percent of their patients received chemotherapy. Of the patients who received chemotherapy, 5-year survival was 22 and the number of harvested LNs was frequently less than 12. Lee and colleagues 15 found that fewer than 12 LNs were harvested in 30.5% of patients after preoperative CRT.…”
Section: Discussionmentioning
confidence: 99%